Efficacy and acceptability of interventions for co-occurring PTSD and SUD: A meta-analysis. (December 2021) - Simpson, Tracy L.; Goldberg, Simon B.; Louden, Diana K.N.; Blakey, Shannon M.; Hawn, Sage E.; Lott, Aline; Browne, Kendall C.; Lehavot, Keren; Kaysen, Debra
Abstract: Over the past 20 years, numerous treatments addressing comorbid Posttraumatic Stress Disorder (PTSD) and Substance Use Disorder (SUD) have been developed and tested. The current meta-analysis examined the efficacy and acceptability of the two central treatment types– trauma-focused and non-trauma-focused – compared with all comparators and with cognitive-behavioral manualized SUD treatments immediately post-treatment and at longest follow-up. Twenty-eight randomized clinical trials ( N  = 3247) were included. There were small to large within-group effects for all forms of active treatment ( g s = 0.30–1.11). Trauma-focused but not non-trauma-focused treatments outperformed all comparators on PTSD outcomes at post-treatment. Neither trauma-focused nor non-trauma-focused treatment outperformed all comparators on SUD outcomes at post-treatment. Neither trauma- nor non-trauma-focused treatment outperformed manualized SUD treatments on PTSD outcomes at either time point. Manualized SUD treatments outperformed trauma-focused treatments on SUD outcomes at post-treatment and non-trauma-focused treatments on PTSD outcomes at follow-up. Regarding treatment retention, neither trauma-focused nor non-trauma-focused treatments significantly differed from all comparators or from manualized SUD treatments. Between-group results were largely unchanged in trim-and-fill analyses, but were not robust to fail-safe N. Few moderators were detected. Taken together, results suggest that trauma-focused, non-trauma-focused, and manualized SUD interventions are sound options for individuals with comorbid PTSD/SUD. Highlights: All active treatments reduced PTSD and substance use disorder (SUD) outcomes. Trauma-focused treatments reduced PTSD more than all other comparators. Manualized SUD had similar effects on PTSD as trauma- and non-trauma treatments. Manualized SUD treatment reduced substance use more than trauma-focused treatments.